(untitled) (Journal of Plant Disease Sciences, 2017)
Chickpea ( L.) productivity is affected by different pests Cicer arietinum both at field as well as storage condition. This study was done with an objective of assessing farmers’ knowledge and management practice to reduce pre- and postharvest losses of chickpea. Farmers have different level of knowledge and perception towards the degree of chickpea losses caused by different factors both at pre-and postharvest level. Farmers at Dembia district believed pre-harvest loss due to insect pest was the highest. However, pre-and postharvest loss due to an insect pest, field rodents, and bad weather condition poses the highest risk to chickpea production at W/belesa district and a similar trend was observed among respondents in G/zuria and Takusa districts. All respondent farmers from Dembia district used aluminium phosphide to manage insect pests in a storage condition. In addition to aluminium phosphide, 66.67% of the respondents use proper drying. On the other hand, 16.67% and 8.33% of respondents manage postharvest loss through mixing chickpea with tef and use of insecticides like malathion, respectively. Farmers in surveyed districts considered different factors in selecting management options mainly the price, efficacy, easiness and their previous experience. Moreover, it was observed that the highest gap among respondents in surveyed districts were on identification and management of insect pests, use of pesticides and on their safety and handling. Therefore, future training and awareness creation should be prepared by assessing farmers’ gap.